2006
DOI: 10.1191/0960327106ht601oa
|View full text |Cite
|
Sign up to set email alerts
|

Terminalia chebula (fruit) prevents liver toxicity caused by sub-chronic administration of rifampicin, isoniazid and pyrazinamide in combination

Abstract: Terminalia chebula Gertn. (Combetraceae) is an important herbal drug in Ayurvedic pharmacopea. In the present study, a 95% ethanolic extract of T. chebula (fruit) (TC extract), which was chemically characterized on the basis of chebuloside II as a marker, was investigated for hepatoprotective activity against anti-tuberculosis (anti-TB) drug-induced toxicity. TC extract was found to prevent the hepatotoxicity caused by the administration of rifampicin (RIF), isoniazid (INH) and pyrazinamide (PZA) (in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 25 publications
4
58
1
Order By: Relevance
“…2-4. Available literatures have shown that extracts obtained from several plants have hepatoprotective activities against the toxicity induced by xenobiotics, including those that are used in the treatment of tuberculosis [28]. The result obtained in this work indicates that the hepatoprotective effect of garlic is dose dependent but not on the duration of garlic intake.…”
Section: Discussionsupporting
confidence: 67%
“…2-4. Available literatures have shown that extracts obtained from several plants have hepatoprotective activities against the toxicity induced by xenobiotics, including those that are used in the treatment of tuberculosis [28]. The result obtained in this work indicates that the hepatoprotective effect of garlic is dose dependent but not on the duration of garlic intake.…”
Section: Discussionsupporting
confidence: 67%
“…Ethanol extract T. chebula was found to prevent the hepatotoxiocity caused by the adminstration of rifampicin, isoniazid and pyrazinamide (combination) in sub-chronic model (12 weeks) [37] . Protective effects of an aqueous extract of T. chebula fruit on the tert-butyl hydroperoxide-induced oxidative injury was observed in cultured rat primary hepatocytes and rat liver have also been documented [28,29] .…”
Section: Hepatoprotective Activitymentioning
confidence: 99%
“…F rom the literature it has been noted that T. chebula exhibited significant hepatoprotective [36][37][38] , cardioprotective [39,40] , antimutagenic/anticarcinogenic [31-3 3 ] , c y t o p r o t e c t i v e [ 4 1 -4 4 ] , a n t i o x i d a n t [ 2 4 -3 0 ] a n d adaptogenic [77,78] effects. Aqueous, ethanol, and ethyl acetate extracts of T. chebula fruits also demonstrated no cellular toxicity on sheep erythrocytes as well as acute oral toxic effects on rats at recommended and higher doses [48,91,92] .…”
Section: Safety Evaluationmentioning
confidence: 99%
“…35 Literature survey revealed that, the CP is one of the many plants have the potential to be used for hepatoprotective effects against the drug or chemical-induced hepatotoxicity. 36,37 CP is one of the plants used to protect the liver injury. Flavonoids are the active constituents of the fl ower of CP act as antioxidants against the reactive oxygen moieties by boosting the endogenous scavenging system of the body, these are also known to interfere various free-radical producing systems and also enhance the endogenous antioxidant function.…”
Section: Resultsmentioning
confidence: 99%